Kepemimpinan Situasional Kepala Sekolah Dalam Mencapai Keberhasilan Pelaksanaan Kurikulum Merdeka Pada Lembaga Pendidikan - Fanani, Muhammad Adip (Proceedings Series of Educational Studies, 2024)
Abstract Along with the development of the times education is required to continue to make improvements and developments, challenges and global competition require educational institutions to be able to produce quality graduates and be able to compete in the labour market. One of the government's efforts to answer these challenges is by issuing an independent curriculum policy. The successful implementation of the independent curriculum is inseparable from the leadership role of the school principal in educational institutions. One of the effective leadership to obtain the success of the independent curriculum is situational leadership. The writing of this article aims to find out the concept of situational leadership, situational leadership models and their application in educational institutions. The writing of this article uses a literature study method (library reseacrh) conducted by examining various theories related to situational leadership in educational institutions. Based on the study conducted, the results obtained are that 1) Situational leadership is said to be effective depending on the conditions and factors of the situation such as the relationship between leaders and subordinates, task structure, position strength, level of readiness or maturity of subordinates. 2) There are various situational leadership models that can be used as a basis for development and help school principals in deciding their leadership style 3) The application of situational leadership in educational institutions has proven effective in improving teacher performance in implementing the independent curriculum and has implications for improving the quality of educational institutions. Abstrak Seiring dengan berkembangannya zaman pendidikan dituntut terus untuk melakukan perbaikan dan pengembangan, tantangan dan persaingan global menuntut lembaga pendidikan untuk mampu menghasilkan lulusan yang berkualitas dan mampu bersaing pada pasar kerja. Salah satu upaya pemerintah untuk menjawab tantangan tersebut dengan mengeluarkan kebijakan kurikulum merdeka. Keberhasilan pelaksanaan kurikulum merdeka tidak terlepas dari peran kepemimpinan Kepala sekolah dalam lembaga lembaga pendidikan. Salah satu kepemimpinan yang efektif untuk memperoleh kesuksesan kurikulum merdeka yaitu kepemipinan situasional. Penulisan artikel ini bertujuan untuk mengetahui konsep kepemimpinan sitasional, model-model kepemimpinan situasional serta penerapannya pada lembaga pendidikan. Penulisan artikel ini menggunakan metode studi literatur (library reseacrh) yang dilakukan dengan mengkaji berbagai teori-teori yang berikaitan dengan kepemimpinan situasional pada lembaga pendidikan. Berdasarkan kajian yang dilakukan diperoleh hasil bahwa 1) Kepemimpinan situasional dikatakan efektif tergantung pada kondisi dan faktor-faktor situasi seperti hubungan antara pemimpin dengan bawahan, struktur tugas, kekuatan posisi, tingkat kesiapan atau kematangan bawahan. 2) Terdapat berbagai model kepempinan situasional yang dapat dijadikan dasar pengembangan dan membantu para kepala sekolah dalam memutuskan gaya kepemimpinanya 3) Penerapan kepemimpinan situasional pada lembaga pendidikan terbukti efektif meningkatkan kinerja guru dalam penerapan kurikulum merdeka dan berimplikasi pada peningkatan kualitas lembaga pendidikan.